Analysis of Variables Affecting on JCO's Consumer Decision (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
JCO is a restaurant and franchise specializing in donuts, frozen yogurt, and coffee. JCO Donuts & Coffee is ownedand managed by Johnny Andrean Group, inspired by Dunkin Donut. The restaurant produces different shapes and flavors, witha particular focus on the quality of basic ingredients and the production process. With this product, JCO has attracted manycustomers. This research conducted what variables influence purchasing decisions. For this reason, variables in the marketingmix are determined, namely product, price, place, and promotion which are thought to influence purchasing decisions. Thisstudy uses primary data, using a questionnaire. The respondents of this study were JCO customers, who were randomlyassigned to 250 respondents. The analytical tool used is multiple regression by first testing the validity and reliability of thedata. The results of the study indicate that the product, price, place, and promotion have positive and significant influence, bothpartially and simultaneously on purchasing decisions.